Schizophrenia plausible protective effect of microRNA-137 is potentially related to estrogen and prolactin in female patients - Peng, Qian; Dai, Zhun; Yin, Jingwen; Lv, Dong; Luo, Xudong; Xiong, Susu; Yang, Zhijiang; Chen, Guangmin; Wei, Yaxue; Wang, Ying; Zhang, Dandan; Wang, Lulu; et al. (Frontiers in Psychiatry, 2023)
Background: Schizophrenia (SCZ) is a serious chronic mental disorder. Our previous case-control genetic association study has shown that microRNA-137 (miR-137) may only protects females against SCZ. Since the important female sex hormone estrogen exerts neuroprotective effects, the relationships between estrogen and miR-137 in pathophysiology of SCZ was further studied in this study.Methods: Genotyping of single-nucleotide polymorphism rs1625579 of miR-137 gene in 1004 SCZ patients and 896 healthy controls were conducted using iMLDR assay. The effect of estradiol (E2) on miR-137 expression was evaluated on human mammary adenocarcinoma cell line (MCF-7) and mouse hippocampal neuron cell line (HT22). The relationships between serum E2 as well as prolactin (PRL) and peripheral blood miR-137 were investigated in 41 SCZ patients and 43 healthy controls. The miR-137 and other reference miRNAs were detected by real-time fluorescent quantitative reverse transcription-PCR.Results: Based on the well-known SNP rs1625579, the distributions of protective genotypes and allele of the miR-137 gene were not different between patients and healthy controls, but were marginally significantly lower in female patients. E2 upregulated the expression of miR-137 to 2.83 and 1.81 times in MCF-7 and HT22 cells, respectively. Both serum E2 and blood miR-137 were significantly decreased or downregulated in SCZ patients, but they lacked of expected positive correlations with each other in both patients and controls. When stratified by sex, blood miR-137 was even negatively correlated with serum E2 in female patients. On the other hand, serum PRL was This is a provisional file, not the final typeset article significantly increased in SCZ patients, and the female patients had the highest serum PRL level and a negative correlation between serum PRL and blood miR-137.The plausible SCZ-protective effect of miR-137 may beis female-specific, of which the underlying mechanism may be that E2 upregulates the expression of miR-137. This protective mechanism may also beis abrogated possibly by elevated PRL in female patients. These preliminary findings reveal suggest a new genetic/environmental interaction mechanism for E2/miR-137 to protect normal females against SCZ and a novel E2/PRL/miR-137-related pathophysiology of female SCZ, implying some new antipsychotic ways for female patients in the future.